Implementasi Good Governance dalam Pengelolaan Keuangan Desa di desa Tempeh Kidul kecamatan Tempeh kabupaten Lumajang - mimin yatminiwati (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2019)
This study aims to describe Good Governance in the Management of Village Revenue and Expenditure Budget in Tempeh Kidul Village, Tempeh District, Lumajang Regency. The object of this research is the Implementation of Good Governance in the Management of Village Revenue and Expenditure Budget in Tempeh Kidul village, Tempeh sub-district, Lumajang district. In this study, the authors used a type of qualitative research with a case study approach. Data collection techniques used were interviews, documentation observation. The data analysis technique used is an interactive analysis model that includes four components, namely data collection, data reduction, data presentation, and verification. The results showed that 1) APB Planning in Tempeh Kidul Village in planning village financial management was quite good. 2) The overall implementation of the financial activities in the village of Tempeh Kidul is well implemented. 3) The implementation of the principles of Good Governance in the management of the APB in the Tempeh Kidul Village has been carried out quite well by the village government.